Supply Chain Cost Reduction using Mitigation & Resilient Strategies in the Hypermarket Retail Business - Veera Pandiyan Kaliani Sundram; Mohan Selvaraju; Prashanth Beleya (International Journal of Supply Chain Management, 2017)
Retail businesses have become more challenging owing to the external and internal forces due to the ever evolving nature of the environment. Various measures are being taken to address the need to manage cost. The supply chain factors must not be ignored as the entire link along the retail supply chain play vital roles. This article is an attempt at presenting an overview of the current situation of the retail environment particularly in the hypermarket sector and the forces affecting their business cost which include knowledge, forecasting, procurement, and sourcing. The paper concludes through literature review that recognizes risks associated with each force that could potentially determine the cost of business for the hypermarkets. As such, an empirical study is to follow this conceptual study to analyse the hypotheses developed and to significantly identify the factors and strategies that retailers could use to reduce the impact of supply chain disruptions to their overall cost.